Predictors of adults' body mass index and the association with index child's infant birth weight, in the Lifeways Cross-Generation Cohort Study of a thousand families in the Republic of Ireland. (22nd June 2017) - McKey, S.; Heinen, M.; Mehegan, J.; Somerville, R.; Khalil, H.; Segurado, R.; Murrin, C.; Kelleher, C. C.
Abstract : The Lifeways study is novel in having information on three generations of the same families. It is well established that infant birth weight (IBW) predicts individuals' risk of adult chronic disease and more recently studies report cross-generation transmission of risk patterns. The aims of this analysis were to examine whether adults' birth weights were associated with measures of own health status or social position and to relate adults' birth weights to that of the index child's IBW. Finally, we assessed whether birth weight of either adults or children was associated with adult body mass index (BMI) of parents and grandparents. We included 1075 children whose IBW was recorded at recruitment from hospital records and 2546 adult cohort members followed from 2001 until 2014. At baseline, a sub-group of 920 adults had reported own birth weight (RBW). Results showed male adults' RBW were significantly higher than females' ( P =0.001). Mothers' RBW was significantly correlated with IBW ( r =0.178, P <0.001). In mixed effects linear models with BMI as the outcome variable, of all adults, and in sub-groups of adults with RBW and of mothers only, the IBW was associated with adult BMI adjusting for other predictors. Adults' BMI was positively associated with age ( P =0.013), index child's IBW ( P =0.001), gender ( P <0.001) but not own RBW, adjusting for family identification number. When mothers were removed from the adult models however, IBW ceased to be associated with BMI, a final model showed RBW being associated with adult BMI ( P =0.04). There are cross-generational associations in the Lifeways cohort, the maternal association being stronger.